Komunikasi Kesehatan dan Pelanggaran Harapan Pasien Medan yang Berobat di Penang Malaysia - Putri, Sri Nurhafmi Widia Hermawan; Nurbani; Kurniawati, Dewi (Jurnal Komunikasi Nusantara, 2025)
The phenomenon of increasing numbers of Indonesian patients, particularly from Medan, choosing to seek medical treatment in Penang, Malaysia, is the focus of this study. Departing from unmet expectations regarding domestic healthcare services, this study aims to understand the communication between patients and medical personnel, as well as the factors that drive patients to choose overseas services. A qualitative method with a phenomenological approach was used to gain an in-depth understanding of the patients' experiences. Data was collected through in-depth interviews with five patients from Medan selected through purposive sampling based on the criterion of having undergone at least three independent medical treatments in Penang. Data triangulation involved a doctor to enrich perspectives and enhance the validity of findings. The study revealed that ineffective communication and lack of empathy in local hospitals led to patient dissatisfaction, prompting them to seek more patient-friendly, transparent, and professional services in Penang. Cost, ease of access, and cultural similarities further reinforce this decision. This study underscores the importance of improving communication and medical professionalism in Indonesia to reduce unmet expectations and decrease the number of patients seeking treatment abroad. Abstrak Fenomena peningkatan pasien asal Indonesia, terutama dari Medan, yang memilih berobat ke Penang, Malaysia, menjadi fokus penelitian ini. Berangkat dari pelanggaran harapan terhadap layanan kesehatan domestik, penelitian ini bertujuan memahami komunikasi antara pasien dan tenaga medis serta faktor yang mendorong pasien memilih layanan luar negeri. Metode yang digunakan adalah kualitatif dengan pendekatan fenomenologi, memungkinkan pemahaman mendalam pengalaman pasien. Data dikumpulkan lewat wawancara mendalam dengan lima pasien Medan yang dipilih secara purposive sampling berdasarkan kriteria pengalaman minimal tigakali berobat ke Penang secara mandiri. Triangulasi data melibatkan seorang dokter untuk memperkaya perspektif dan meningkatkan validitas temuan. Hasil penelitian mengungkap bahwa komunikasi yang kurang efektif dan empati di rumah sakit lokal menyebabkan ketidakpuasan pasien, sehingga mereka mencari layanan yang lebih ramah, transparan, dan profesional di Penang. Faktor biaya, akses mudah, dan kesamaan budaya turut memperkuat keputusan tersebut. Studi ini menegaskan pentingnya peningkatan komunikasi dan profesionalisme medis di Indonesia guna menekan pelanggaran harapan dan mengurangi pasien yang berobat ke luar negeri.